2013
DOI: 10.1038/eye.2013.204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of foveal-sparing with foveal-involving photodynamic therapy for myopic choroidal neovascularization

Abstract: Purpose To evaluate the visual outcomes of choroidal neovascularization (CNV) secondary to pathological myopia in eyes treated with photodynamic therapy (PDT), and to determine the effect of lesion location and foveal involvement on visual prognosis. Methods Interventional case series of 24 consecutive patients with myopic CNV treated with PDT. The main outcome measure was final LogMAR visual acuity (VA). Results Of 24 eyes, the CNV lesion was subfoveal in 11 and extrafoveal in 13. Overall, the mean LogMAR VA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…With regard to extrafoveal myopic choroidal neovascularization (mCNV), we agree with Chew and Tan about a continuing role for photodynamic therapy in this patient category [2]. Our population was composed of subfoveal and juxtafoveal mCNV.…”
mentioning
confidence: 48%
“…With regard to extrafoveal myopic choroidal neovascularization (mCNV), we agree with Chew and Tan about a continuing role for photodynamic therapy in this patient category [2]. Our population was composed of subfoveal and juxtafoveal mCNV.…”
mentioning
confidence: 48%
“…al. [3] recently demonstrated that if the PDT laser spot does not involve the center of the fovea in extrafoveal mCNV, the visual outcomes are comparable to longterm studies using anti-VEGF therapy. In that series, mean LogMAR VA of 0.26 was achieved at 24 months [3].…”
mentioning
confidence: 91%
“…[3] recently demonstrated that if the PDT laser spot does not involve the center of the fovea in extrafoveal mCNV, the visual outcomes are comparable to longterm studies using anti-VEGF therapy. In that series, mean LogMAR VA of 0.26 was achieved at 24 months [3]. Furthermore, while anti-VEGF therapy has been shown to be effective [1], it is also associated with both ocular and systemic risks [4] such as endophthalmitis and cerebrovascular accidents.…”
mentioning
confidence: 91%
See 2 more Smart Citations